Electron and photon responses of CWO scintillation crystal. (December 2021) - Jomkaew, T.; Chaiphaksa, W.; Siengsanoh, K.; Limkitjaroenporn, P.; Kedkaew, C.; Kim, H.J.; Kothan, S.; Prasatkhetragarn, A.; Kaewkhao, J.
Abstract: The electron response and photon response of cadmium tungstate crystal (CWO) scintillation crystal have been investigated. For the photon response measurement, the 133 Ba, 22 Na, 137 Cs and 60 Co were used as radioactive sources in the energy range of 356–1332 keV. For the electron response measurement, the 137 Cs source with gamma energy at 662 keV was used for the measurement of the coincidence electron energy spectra at seven scattering angles from 30° to 120°. The seven consistent electron energies were found in the range of 101.27–443.27 keV. The light yield results for both techniques showed a slight increase when gamma energy increased. Besides, for the energy resolutions and electron energy resolutions, the graph showed the relationship between the electron energy resolution and the inverse of the square root of the electron energy. Highlights: Electron and photon responses of CWO) scrystal were investigated. Photon response, 133 Ba, 22 Na, 137 Cs and 60 Co were used. Coincidence electron energy spectra at seven scattering angles were recorded. Light yield of both techniques showed a slight increase when gamma energy increased. Relationship of electron energy resolution show inverse square root of electron energy.